Kinematic Parameters That Influence the Aesthetic Perception of Beauty in Contemporary Dance. (April 2013) - Torrents, Carlota; Castañer, Marta; Jofre, Toni; Morey, Gaspar; Reverter, Ferran
Some experiments have stablished that certain kinematic parameters can influence the subjective aesthetic perception of the dance audience. Neave, McCarty, Freynik, Caplan, Hönekopp, and Fink (2010, Biology Letters 7 221–224) reported eleven movement parameters in non-expert male dancers, showing a significant positive correlation with perceived dance quality. We aim to identify some of the kinematic parameters of expert dancers' movements that influence the subjective aesthetic perception of observers in relation to specific skills of contemporary dance. Four experienced contemporary dancers performed three repetitions of four dance-related motor skills. Motion was captured by a VICON-MX system. The resulting 48 animations were viewed by 108 observers. The observers judged beauty using a semantic differential. The data were then subjected to multiple factor analysis. The results suggested that there were strong associations between higher beauty scores and certain kinematic parameters, especially those related to amplitude of movement.